PUTUSAN VERSTEK DALAM CERAI GUGAT KARENA PELANGGARAN TAKLIK TALAK DI PENGADILAN AGAMA SAMARINDA - Andaryuni, Lilik (istinbath, 2017)
Abstract: The rising rate of divorce initiated by women (cerai gugat) in East Kalimantan, especially in Samarinda, has been stimulated by many causes, ranging from continuous disharmony, economic problems, love affairs, to lack of spousal responsibility, especially husbands, which constitute the most prominent cause of divorce. By leaving their wife irresponsibly, husbands violatetheconditionsthatcangeneratedivorceclaimbywives.235divorcesout of total 237 cases are concerned with the violation of contingent repudiation (ta’liq talaq). All were decided without defendants’ presence (verstek) except two cases where both plaintiff and defendant were present. This study argues that verstek decision, since it is given in a relatively fast procedure, become the best mechanism for women to seek justice and to end their uncertain status after being neglected by their husband. This is relevant to the court principle where justice is simple, fast and cheap. This principle is laid down in Chapter 4 of Law 48/2009 about Court Power andCompetence. Abstrak: Tingginya angka cerai gugat di Kalimantan Timur khususnya Samarinda, disebabkan banyak faktor, di antaranya ketidakharmonisan, ekonomi, gangguan pihak ketiga dan tidak ada tanggung jawab. Tida ada tanggung jawab ini menjadi penyebab utama terjadinya cerai gugat akibat pelanggaran taklik talak. Hal ini terbukti dari 237 kasus cerai gugat akibat pelanggaran taklik talak 235 kasus atau sekitar 99,16% diputus Verstek, hanya 2 kasus (0,84%) tergugat yang hadir di persidangan. Putusan verstek akibat pelanggaran taklik talak memberikan kemudahan bagi pihak istri dan memberikan kepastian hukum akan nasibnya yang tidak jelas akibat kepergian suamiyangtidakadakabarberitanya.Inisejalandeganazasperadilan sederhana, cepat, dan biaya ringan sebagaimana dalam Pasal 4 ayat (2) UU Nomor 48 Tahun 2009 tentang Kekuasaan Kehakiman.